2020
DOI: 10.1111/1471-0528.16108
|View full text |Cite
|
Sign up to set email alerts
|

Metformin plus megestrol acetate compared with megestrol acetate alone as fertility‐sparing treatment in patients with atypical endometrial hyperplasia and well‐differentiated endometrial cancer: a randomised controlled trial

Abstract: Objective To assess the efficacy of metformin in megestrol acetate (MA)-based fertility-sparing treatment for patients with atypical endometrial hyperplasia (AEH) and endometrioid endometrial cancer (EEC).Design A randomised, single-centre, open-label, controlled trial conducted between October 2013 and December 2017.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 26 publications
1
105
0
Order By: Relevance
“…We suggest that treatment aiming to alleviate endocrine disorders might be helpful to improve fertility-preserving treatment outcome in AEH or EEC patients with PCOS. Metformin, which is commonly used in PCOS patients, has been shown to improve the 16-week CR rate in AEH patients [ 28 ]. One study suggested that metformin along with Diane-35, which has anti-androgenic properties, might be a useful regimen for fertility-preserving treatment in EEC patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that treatment aiming to alleviate endocrine disorders might be helpful to improve fertility-preserving treatment outcome in AEH or EEC patients with PCOS. Metformin, which is commonly used in PCOS patients, has been shown to improve the 16-week CR rate in AEH patients [ 28 ]. One study suggested that metformin along with Diane-35, which has anti-androgenic properties, might be a useful regimen for fertility-preserving treatment in EEC patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various regimens have been proposed as alternative options for treating AEH and EEC, like prolonged treatment duration, Diane-35, metformin, LNG-IUS, GnRH-a, aromatase inhibitors (such as letrozole), etc. [ 5 14 15 16 ]. Several studies have reported improved therapeutic effects through prolonging treatment duration [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because clinical observation and lab research has shown possible cancer inhibiting effect of metformin which might help improve the fertility preserving outcome in EEC and AEH patients [ 14 20 21 22 23 24 25 ]. Our prospective clinical trial demonstrated that metformin plus MA was associated with an improved 16-week CR rate when compared to MA alone in AEH patients [ 14 ]. LNG-IUS provides doses of progestin to the local endometrium that are several times higher than that provided by oral progesterone and have less systemic effects [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a meta-analysis of the above studies supports a greater overall survival in metformin users compared to nonusers [ 133 ], although the low number of studies and the lack of randomized studies compromise the evidence level of the meta-analysis. Clinical trials using metformin for atypical endometrial hyperplasia (AEH) or EC have recently accumulated evidence for its efficacy [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. Most studies used the presurgical window approach, in which patients diagnosed by endometrial biopsy were treated with metformin during the period prior to hysterectomy, and some studies targeted patients who underwent fertility-sparing treatments in combination with progestins.…”
Section: What About Metformin? Is the Pi3k-akt Pathway A Target?mentioning
confidence: 99%
“…Most studies evaluated tumor and serum factors in relation to proliferative activity or insulin signaling, and some factors were affected by metformin as expected. Notably, one recent randomized controlled trial of fertility-sparing treatment evaluated the clinical benefit in AEH or EC patients, and found that the complete response rate within 16 weeks of treatment was higher in the metformin plus megestrol group than in the megestrol group (34.3 versus 20.7%, OR 2.0, 95% CI 0.89–4.51, p = 0.09), and the difference was more significant in AEH patients (39.6 versus 20.4%, OR 2.56, 95% CI 1.06–6.21, p = 0.04) [ 146 ]. Few clinical trials have been reported for advanced or recurrent ECs, but a phase 2/3 trial by the Gynecologic Oncology Group for advanced or recurrent EC (NCT02065687) is ongoing and is comparing paclitaxel/carboplatin alone or in combination with metformin as first-line chemotherapy.…”
Section: What About Metformin? Is the Pi3k-akt Pathway A Target?mentioning
confidence: 99%